Assessing the Europeanisation of Turkey domestic politics: To what extent has candidate status transformed the military control over civilian rule in Turkey? - Oney, Bilge; Halilsoy, Pinar (Academic Journals, 2011)
The relationship between the European Union (EU) and Turkey can go back to 1963, the Ankara Agreement, aiming the accession of Turkey to the European Economic Community. For more than two decades after 1963, Turkish political life has been very unstable and interrupted with military interventions. In 1987, Turkey applied for the full EU membership and a candidacy status was granted to her in 1999, in Helsinki Summit. With candidacy status, Turkey has to improve the functioning of its domestic political and democratic structure to become eligible for full membership. This article seeks to assess the impact of EU on Turkish domestic politics with specific focus on the civil-military relations after Turkey gained candidate status. The theory of top-down Europeanisation is employed to assess EU-level pressure on domestic political and democratic structure of Turkey. Since Turkey is a candidate country, this pressure on Turkey emerges through EU conditionality policy-tool which has become quite important after the Copenhagen process in 1993.
Keywords: Turkey; European Union; Europeanisation; conditionality; military rule; democratisation